Bureaucratic Identity and the Shape of Public Policy: A Game Theoretic Analysis - Shaheen Naseer; Klaus Heine (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
The paper proposes a theoretical framework to explain policy drift, when identity moderates the principle-agent relation between the legislator and the bureaucracy. Our model points to the subtle interaction between different administrative levels of bureaucracy and how this interaction shapes the structure and size of budgetary allocations. Conceptually we enrich the public choice tradition of modeling bureaucracies by insights which fall broadly into the study of organizational behavior.
Keywords: D73; H11; 330